Appendiceal carcinoid in a pediatric patient with Peutz-Jeghers syndrome: A case report and comprehensive literature review. Issue 39 (1st October 2021) - Zvizdic, Zlatan; Milisic, Emir; Ibisevic, Nermina; Pasic, Irmina Sefic; Vranic, Semir
Abstract: Rationale: Peutz-Jeghers syndrome (PJS), a rare autosomal dominant disorder, is characterized by mucocutaneous pigmentations, hamartomatous polyps in the gastrointestinal tract, and a high risk of developing various malignancies. To the best of our knowledge, only 1 case of appendiceal carcinoid associated with PJS has been previously reported in the pediatric population. Patient concerns: We report a 7-year-old girl who was admitted for severe, intermittent abdominal pain and cramps, nausea, and vomiting. Multiple brown melanotic macules on the lips, buccal mucosa, and the tongue were noted. Diagnosis: A plain abdominal X-ray in a standing position revealed dilated intestinal loops with multiple air-fluid levels. A computed tomography scan of the abdomen showing a "coffee bean" appearance of the jejunal loop with a transition point to the duodenal loop. Axial-contrast-enhanced computed tomography scan of the abdomen showing dilated jejunum loops, filled with fluid with the swirled appearance of mesentery typical for volvulus. The diagnosis of PJS was based on clinical findings along with the histopathologic confirmation of the hamartomatous polyps. Interventions: An emergency laparotomy was performed, revealing a jejunojejunal intussusception starting 40 cm from the duodenojejunal flexure. Jejunotomy revealed that a lead-point intussusception was a necrotic hamartomatous polyp. After resecting the involved jejunal necrotic segment, including the polyp, end-to-end jejuno-jejunal anastomosis was performed. Further exploration revealed the presence of a jejunal mass 80 cm from the duodenojejunal flexure identified as another hamartomatous pedunculated polyp. The polyp was resected, and the enterotomy was then closed transversely. The grossly normal appendix was also removed. Outcomes: Clinical findings along with the histopathologically confirmed hamartomatous polyps were consistent with PJS. An appendiceal carcinoid (well-differentiated neuroendocrine tumor, European Neuroendocrine Tumor Society stage pT2) was incidentally detected during histological examination of the appendix. The patient and parents were counseled accordingly, focusing on active surveillance and control of symptoms. Two additional hamartomatous polyps (gastric and jejunal) were detected endoscopically and resected in the fourth postoperative week. A regular, 1-year follow-up and surveillance revealed no complications or recurrences. Lessons: Unusual neoplasms can occasionally be encountered in well-defined syndromes such as PJS. Therefore, active follow-up and surveillance are mandatory for all patients with PJS.